ENHANCING SPIRITUAL CARE IN NURSING PRACTICE: EXPLORING THE RELATIONSHIP BETWEEN IMPLEMENTATION OF SPIRITUAL ASPECTS AND FULFILLMENT OF PATIENTS' SPIRITUAL NEEDS - Aris Citra Wisuda, Aris Citra Wisuda; Tukimin bin Sansuwito; Citra Suraya; Dian Emiliasari (Citra Internasional Institute, 2024)
Background: Nurses are integral to comprehensive patient care, addressing biological, psychological, social, and spiritual dimensions. Spiritual care is a crucial component of nursing, ensuring patients' holistic well-being. Objective: This study explores the link between nurses' spiritual application and inpatients' spiritual fulfillment. Method: Conducted at Siti Khadijah Islamic Hospital, Palembang from October to December 2023, this quantitative research sampled 42 inpatients through simple random sampling. Data collected via questionnaires were analyzed using univariate and bivariate methods (chi-square). Instruments included